Kontribusi buku edupark fisika mifan waterpark padang panjang untuk meremediasi miskonsepsi siswa materi usaha dan energi di kelas X IPA SMAN 1 2x11 Kayutanam - Dian Syahfitri; HAMDI HAMDI; DEWI PUSPA SARI (Universitas Negeri Padang, 2020)
The purpose of the research was to knowed the effectiveness of remediation by using Edupark Mifan Waterpark Padang Panjang book on work and energy in 1 2x11 Kayutanam grade X students at the Kayutanam I Government Secondary School. Using intact group method students from the class X IPA 3 academic year 2019/2020 was chosen to participate in the one group pretest-posttest experimental design. The instrument of the research was diagnostics test. The population of the research was all students of 1 2x11 Kayutanam Junior High School grade X while samples selected through intact group technique consisted of 27 students in grade X IPA 3. The results showed that the Edupark MiFan Waterpark Padang Panjang effective to remedial student misconception with the effectiveness categorized was medium as much as 0,34 of each student, as much as 0,31 of each concept. The average of student misconception reduction percentage was as much as 34,41% of each student and 30,81% of each concept. Application Edupark Mifan Waterpark Padang Panjang book effective to reduce student misconception. With the result that remediation using Edupark Mifan Waterpark Padang Panjang book can be use as an alternative to repaired student misconception on learning process.